Design and numerical simulation of a semi-cast-in-situ synthetic material sports surface on shock absorption performance optimization - Hong Wang; Pan Zhang; Weitao Zheng; Gan Liu; Yong Ma; Rui Han (PLoS ONE, 2025)
The persistent issue of moisture-induced “heave” in synthetic sports surfaces can affect athlete safety and surface performance. The objective of the study was to design an innovative synthetic material athletic track structure that mitigates adhesive failure between the synthetic layer and the cement base due to underground moisture. The new structure ensures field safety and meets biomechanical requirements for performance and shock absorption. Numerical simulation methods are employed to analyze the shock absorption performance of the synthetic material track and field facility, incorporating the new structure, and subsequently to propose optimization strategies for the structural design. The optimal structure adopted a circular casting hole design, with a cast-in-situ surface layer thickness of 12 mm, a prefabricated surface layer thickness of 6 mm, a hole diameter of 45 mm, and a hole spacing of 80 mm arranged in a square pattern. The results indicated that the proposed structure not only met the required standards for shock absorption, but also offered a promising solution to the issue of moisture-induced “heave” prevalent in traditional sports surfaces. The study provided important theoretical support and practical guidance for the scientific and efficient construction of athletic tracks.